Android-based Kasih Ibu application for postpartum mothers using the research and development method - Subriah Subriah; Zulaeha A. Amdadi; Andi Wilda Arianggara; Agustina Ningsih (PAGEPress Publications, 2024)
Endorphin massage is a light massage technique performed to help milk production. The purpose of this study is to develop the application of Kasih Ibu as a medium of education that can support the application of Endorphin Massage. The method used in this study is Research and Development (RnD) with Brog and Gall models. The subjects of the research are two media experts, two material experts, and 40 postpartum mothers. The results showed that the validation test results from material experts averaged 92% and validation results from media experts averaged 87%, which showed that the Kasih Ibu application was very feasible to use. Test user validity using a TAM (Technology Acceptance Model) questionnaire. Small-scale trials resulted in 95% and large-scale trials resulted in 96% with the very Worth it category. The Kasih Ibu application as a medium of Education and Communication is very worthy of use and can be accepted by postpartum mothers.